The Effect of Transcranial Direct Current Stimulation (tDCS) on Mood and Emotional Self-Regulation in Individuals with Generalized Anxiety Disorder - Mofidi Tabatabaei, Nayer; Kazemi, Amaneh Sadat; Hasani Abharin, Peyman; Lotfi Kashani, Farah (KMAN Counseling & Psychology Nexus, 2025)
The present study aimed to investigate the effect of transcranial direct current stimulation (tDCS) on mood and emotional self-regulation in individuals with generalized anxiety disorder (GAD). The statistical population included all individuals with anxiety who referred to the Behjoo Clinic in Tehran during 2024. This research employed a quasi-experimental design with pre-test, post-test, and follow-up phases, along with a control group. Data were collected using the Pennsylvania State Worry Questionnaire (1990), the Positive and Negative Affect Schedule (1980), the Emotion Regulation Questionnaire by Garnefski et al. (2001), and the Stroop Test (1935). The tDCS intervention was conducted over 15 sessions (three sessions per week), with each session lasting 20 minutes, while the control group received no intervention. Data analysis was performed using repeated-measures ANOVA with SPSS-26 software. The findings revealed that tDCS significantly improved mood and emotional self-regulation in individuals with anxiety (P < 0.05). Therefore, it can be concluded that tDCS is an effective intervention for enhancing mood and emotional self-regulation in individuals with generalized anxiety disorder.